Analisa Pengelolaan Kas dalam Upaya untuk Menjaga Likuiditas pada Koperasi Agribisnis Dana Mulya Pacet - Ningsih, Veryda ayu; Nasution, Ute; Mulyati, Diana (Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractThe importance of cash management to manage effectively and efficientlyshort-term cash flows and existing cooperative cash balances by first looking at cash inflows and cash outflows,cashinflowsandcashoutflowswilloccurcontinuouslythroughoutthecooperative's lifetime. If the availability of cash is less then the cooperative cannot be optimal in carrying out its operational activities, whereas if the cooperative has excess cash it is also not good in its operational activities. Cash management is measured by analyzing cash inflows and cash outflows. This study aims to describe the analysis of cash management of liquidity in the Koperasi Agribisnis Dana Mulya Pacet. This type of research is a descriptive study with a quantitative approach. While the object of this research is the financial statements of the Koperasi Agribisnis Dana Mulya Pacet, located on Jl. Raya Pacet No. 5, Desa Pacet , Kecamatan Pacet, Kabupaten Mojokerto. The results revealed that based on an analysis of cash management is quite good, followed by the acquisition of liquidity which is still low and fluctuating every year in the cooperative. The decrease in the liquidity ratio is due to an increase in debt every year.To solve this problem, it is expected that the cooperative will pay more attention to the cash flow and lower the amount of debt so that the management of cash can bemaintained. Keywords :Cash Management, Liquidity